Supervision in Gruppen in der Sozialen Arbeit: Gruppensupervision als Methode zwischen Nähe und Distanz - Marita Katharina Wambach-Schulz (IU Internationale Hochschule, 2021)
– The recent differentiation and professionalisation activities in supervision offer a wealth of equivalence and difference and thus room for ever new research questions and perspectives. The starting point for this discussion paper is a project study on extended, mediation-analogue supervision. This discussion paper aims to shed light on the balancing act of closeness and distance in shaping the relationship between social work professionals and their clients, whereby tensions are likely to characterise practice significantly. Thus, the guiding question is: How can tensions associated with closeness and distance in the shaping of professional relationships be strategically managed by social work professionals with the help of selected supervision methods? The resulting profile of demands for professionals can be worked out in the context of supervision in groups for the resolution of tensions and for strategy expansion. For this purpose, a theoretical, pedagogical action concept and a scenario for practice are presented, which could be used reflexively in a real-time group supervision for practitioners. The theoretical statements and secondary data from studies are contrasted with results from empirical insights from the author's earlier research work. The conclusion should be able to give impulses for new research perspectives.
Keywords: 300; Supervision in Gruppen; Nähe und Distanz; Soziale Arbeit; Spannungsfeld; Strategien-Erweiterung